황해 직선 항로상 대기오염물질의 측정 - 이승복; 배귀남; 김영성; 문길주; 심상규; 진현철 (한국대기환경학회, 2004)
Air pollutants were measured eight times from June 1999 to June 2002 on regular ferries cruising across the Yellow Sea between Incheon in Korea and Qingdao or Tianjin in China. PM10 and PM2.5 were measured as particulate matters and SO2, CO, and NOx were measured as gaseous pollutants. On each route, sampling was made, starting two hour after departure and ending two hour before arrival. Low concentrations of gaseous pollutants that were not much varied according to sampling period and location revealed that atmosphere over the sea was not directly affected by anthropogenic emissions. However, concentrations of fine particles were generally higher than those measured at Deokjeok Island. 50 km west of the western seashore, at similar periods. It was believed that considerable influence of China in the form of secondary pollutants was exerted over the sea.